Robotic perineal radical prostatectomy and pelvic lymph node dissection using a purpose‐built single‐port robotic platform. (3rd September 2016) - Ramirez, Daniel; Maurice, Matthew J.; Kaouk, Jihad H.
Abstract : Objectives: To describe the features of the novel, purpose‐built da Vinci model SP1098 single‐port robotic platform and to describe a step‐by‐step approach for perineal prostatectomy and pelvic lymph node dissection in a cadaver model. Methods: Three single‐port robotic radical perineal prostatectomies and two pelvic lymph node dissections were performed on three male cadavers to assess the feasibility of the SP1098 da Vinci robotic platform. The steps in the procedure included division of the rectourethralis muscle, splitting of the levator ani muscles bilaterally, opening of Denonvilliers fascia with dissection of the seminal vesicles, apical dissection and urethral division, anterior and lateral dissection with ligation of prostatic pedicles, bilateral pelvic lymph node dissection, and creation of the new vesico‐urethral anastomosis. The main outcomes assessed were operating time per step, total operating time, intra‐operative complications and need for conversion to conventional or open techniques. Results: No conversions were required. No intra‐operative complications were seen. The median (range) operating time for performing single‐port robotic radical perineal prostatectomy and pelvic lymph node dissection was 210 (180–240) min. Conclusions: We have shown the feasibility and efficacy of a novel, purpose‐built robotic system in performing single‐port radical perineal prostatectomy and describe, for the first time, the feasibility of robotic perineal lymph node dissection. This single‐port system will facilitate single‐port applications and allow surgeons to perform major urological operations via a small, single incision while preserving triangulation and optics, and eliminating clashing between instruments. Future clinical studies are needed to support these encouraging outcomes.